Antibacterial Activity of Glutathione-Stabilized Silver Nanoparticles Against Campylobacter Multidrug-Resistant Strains - Silvan, Jose M.; Zorraquin-Peña, Irene; Gonzalez de Llano, Dolores; Moreno-Arribas, M. Victoria; Martinez-Rodriguez, Adolfo J. (Frontiers in Microbiology, 2018)
Campylobacter is the leading cause of bacterial diarrheal disease worldwide. Although most episodes of campylobacteriosis are self-limiting, antibiotic treatment is usually needed in patients with serious enteritis, and especially in childrens or the elderly. In the last years, antibiotic resistance in Campylobacter has become a major public health concern and a great interest exists in developing new antimicrobial strategies for reducing the impact of this food-borne pathogen on human health. Among them, the use of silver nanoparticles as antibacterial agents has taken on increased importance in the field of medicine. The aim of the present study was to evaluate the antimicrobial effectiveness of glutathione-stabilized silver nanoparticles (GSH-Ag NPs) against multidrug resistant (MDR) Campylobacter strains isolated from the chicken food chain (FC) and clinical patients (C). The results obtained showed that GSH-Ag NPs were highly effective against all MDR Campylobacter strains tested. The minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were in a range from 4.92 to 39.4 µg/mL and 9.85 to 39.4 µg/mL, respectively. Cytotoxicity assays were also assessed using human intestinal HT-29, Caco-2, and CCD-18 epithelial cells. Exposure of GSH-Ag NPs to intestinal cells showed a dose-dependent cytotoxic effect in all cell lines between 9.85 and 39.4 µg/mL. More than 60% of the tested Campylobacter strains were susceptible to GSH-Ag NPs concentrations ≤ 9.85 μg/mL, suggesting that practical inhibitory levels could be reached at low GSH-Ag NPs concentrations. Further works are needed with the purpose to evaluate the practical implications of the toxicity studies and to know more about other attributes linked to the biological compatibility. This behaviour makes GSH-Ag NPs as a promising tool for the design of novel antibacterial agents for controlling Campylobacter.